2022
DOI: 10.3389/fneur.2022.922535
|View full text |Cite
|
Sign up to set email alerts
|

The clinical correlation between Alzheimer's disease and epilepsy

Abstract: Alzheimer's disease and epilepsy are common nervous system diseases in older adults, and their incidence rates tend to increase with age. Patients with mild cognitive impairment and Alzheimer's disease are more prone to have seizures. In patients older than 65 years, neurodegenerative conditions accounted for ~10% of all late-onset epilepsy cases, most of which are Alzheimer's disease. Epilepsy and seizure can occur in the early and late stages of Alzheimer's disease, leading to functional deterioration and be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 116 publications
1
12
0
Order By: Relevance
“…The underlying molecular and cellular mechanisms of this might, however, be manifold, including dysfunction of GABAergic inhibitory neurons as well as enhanced excitability of pyramidal neurons ( 6 , 7 ). PTZ is commonly used to probe for an epileptic phenotype in models of CNS disorders, including AD ( 33 ), given that about 10% of AD cases display epileptic discharges or seizures ( 50 ). To the best of our knowledge, such a comorbidity has never been described in ALS, and no common genetic risk has been reported ( 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…The underlying molecular and cellular mechanisms of this might, however, be manifold, including dysfunction of GABAergic inhibitory neurons as well as enhanced excitability of pyramidal neurons ( 6 , 7 ). PTZ is commonly used to probe for an epileptic phenotype in models of CNS disorders, including AD ( 33 ), given that about 10% of AD cases display epileptic discharges or seizures ( 50 ). To the best of our knowledge, such a comorbidity has never been described in ALS, and no common genetic risk has been reported ( 51 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Overall, these results are indicative of selective vulnerability of inhibitory transmission at early disease stages, and suggest that AMPAR and NMDAR subunit composition is dynamic through AD progression and certain changes could be compensatory or neuroprotective from excitotoxicity, as often seen in acute epilepsy models (Russo et al 2013; Leo et al 2018). Recent epidemiologic research has underscored strong associations between epilepsy, late onset seizures, and AD (Vossel et al 2017; Zhang et al 2022), and while in the past, seizures were assumed to be an unfortunate biproduct of AD, we and others have provided increasing preclinical and clinical evidence that seizures significantly contribute to neuropathology and cognitive decline, and may also be a treatable component of this complex disease. Indeed, in a recent phase 2a clinical trial, levetiracetam, an antiepileptic drug, was shown to improve memory and executive function in AD patients with epileptiform activity (Vossel et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Recent epidemiologic research has underscored strong associations between epilepsy, late onset seizures, and AD 1,107111 . In the past, seizures were assumed to be an unfortunate biproduct of AD.…”
Section: Discussionmentioning
confidence: 99%
“…In individuals with epilepsy of unknown etiology, occult cerebrovascular disease has been proposed as an etiology given the high prevalence of vascular risk factors in this population such as hypertension and diabetes (8,9). Another potential etiology is the shared neuropathology with neurodegenerative disease, including a bidirectional relationship between epilepsy and dementia (3,4,10). Specifically, several prospective and retrospective studies have reported an increased risk of dementia in individuals with epilepsy (11)(12)(13)(14)(15)(16) and increased risk of epilepsy in patients with Alzheimer' s disease (AD) (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%